Летняя сказка. Стихотворение Осипа Мандельштама «Пароходик с петухами...» (1937) - Bobrik, Marina (Wiener Slawistischer Almanach, 2022)
One of Mandelstam’s last surviving poems, “Parokhodik s petukhami... ” (1937), is considered to be one of his most difficult and darkest texts, and yet has never received a convincing interpretation. In this article the poem becomes the subject of close reading from several different positions. Following the pattern of reading the score in musical practice, the analysis starts with a linguistic commentary that allows the reader to restore the coherence of the text necessary for understanding. We then offer a paraphrase of the poem as a working version, which is followed by its interpretation. The reading optics are sequentially tuned to two horizons: first to the context of Mandelstam’s work, then to the cultural background (Zeitgeist) of the 1930s, analysed with reference to some key words of the poem. In my approach I am guided by the idea of the integrity of understanding (accepting that its completeness is unattainable).